2013
DOI: 10.1080/1350293x.2012.760336
|View full text |Cite
|
Sign up to set email alerts
|

Supporting and stimulating the learning of socioeconomically disadvantaged children – perspectives of parents and educators in the transition from preschool to primary school

Abstract: When children move from preschool to primary school in Germany, this involves a transition between two distinct systems with regard to political responsibility. Following Rimm-Kaufman and Pianta's (2000) ecological and dynamic model of transition, the research project focuses on the perspectives of parents and professionals on the learning processes of children from socioeconomically disadvantaged families in the transition from preschool to school. Against the backdrop of a socio-constructive conception of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
(22 reference statements)
0
7
0
2
Order By: Relevance
“…The challenges connected to establishing trusting relationship between parents and professionals seems to be particularly salient when children and families from vulnerable groups are involved. Several studies involving migrant parents (Van Laere et al 2018;Van Laere and Vandenbroeck 2017) as well as socio-economically disadvantaged families (Rothe et al 2014;Arndt et al 2013) revealed thatin spite of a rhetoric of educational partnershipthe more formalised and learning-oriented the educational settings become (ie: from daycare to preschool, from preschool to primary school) the less parents' expertise is valued against that of professionals. In such context of unequal power dynamics, parents' concernsrelated to the social, emotional and physical support available to their children during transitions as well as to their actual belonging and participation in the classroomare often left unheard, undermining the creation of trusting relationship between families and professionals from the outset.…”
Section: European Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The challenges connected to establishing trusting relationship between parents and professionals seems to be particularly salient when children and families from vulnerable groups are involved. Several studies involving migrant parents (Van Laere et al 2018;Van Laere and Vandenbroeck 2017) as well as socio-economically disadvantaged families (Rothe et al 2014;Arndt et al 2013) revealed thatin spite of a rhetoric of educational partnershipthe more formalised and learning-oriented the educational settings become (ie: from daycare to preschool, from preschool to primary school) the less parents' expertise is valued against that of professionals. In such context of unequal power dynamics, parents' concernsrelated to the social, emotional and physical support available to their children during transitions as well as to their actual belonging and participation in the classroomare often left unheard, undermining the creation of trusting relationship between families and professionals from the outset.…”
Section: European Literaturementioning
confidence: 99%
“…Studies carried out in the context of EU Member States indicate that positive experiences of transition between educational levels can be a critical factor in fostering children's development and school success, while negative experiences can produce lasting difficulties leading to under-achievement (Dumčius et al 2014). This seems to be especially the case for children and families from migrant backgrounds or belonging to vulnerable social groups (Council of European Union 2015; OECD 2017): research shows that the way in which transitions are managed tend to unintentionally favour children from more advantaged backgrounds, whose families know how to navigate the educational system including its institutional flaws (Van Laere and Vandenbroeck 2017;Amerijckx and Humblet 2015;Rothe et al 2014;Arndt et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some mothers remained concerned about issues but opportunities to develop the parentteacher relationship continued as these were resolved. Mothers sometimes felt their knowledge was not as valued as the teacher's knowledge and advice (Arndt, Rothe, Urban & Werning, 2013).…”
Section: Opportunitiesmentioning
confidence: 99%
“…The responsible education administrations determine, at a national level, elements that differentiate countries in terms of management of the stages of ECE and PE, and their own guidelines for teacher training (Tomaszewska-Pękała et al, 2017). The macro-level regulates, on the one hand, the factors that facilitate the continuity of the transition: the teacher-student ratio (class size and student-teacher ratio) (Chan, 2010;Lehrer, 2018), the type of groupings (Huf, 2013;Margetts, 2002;Quinn & Hennessy, 2010), the funding of each stage (Greenberg, 2018), and the institutional responsibility for each stage (Arndt et al, 2013). On the other hand, the macro-level also regulates the factors related to teacher training, both for initial and lifelong learning.…”
Section: Introductionmentioning
confidence: 99%